THE PROFESSION ZAKAT AND ITS BENEFITS - Sarbini Anim; Kholis Kohari; Zamakhsyari Abdul Majid; Mohammad Adnan (El-Arbah: Jurnal Ekonomi, Bisnis Dan Perbankan Syariah, 2021)
Professional zakat is zakat that is imposed on each job or certain professional expertise, either done alone or in conjunction with other people / institutions, which is done alone or together with other people/institutions, which brings income (money) that meets the nisab (minimum limit to be able to pay zakat). income (money) that meets the nisab (minimum limit to be able to pay zakat). to be able to pay zakat). This article tries to explain about professional zakat and its benefits to society.for the community. Zakat profesi adalah zakat yang dikenakan pada tiap pekerjaan atau keahlian profesional tertentu, baik yang dilakukan sendiri maupun yang dilakukan bersama dengan orang/lembaga lain, yang mendatangkan penghasilan (uang) yang memenuhi nisab (batas minimum untuk bisa berzakat). Artikel ini mencoba memaparkan tentang zakat profesi dan manfaatnya bagi masyarakat.